Discrete Choice Experiment Response Rates: A Meta‐analysis. (27th April 2016) - Watson, Verity; Becker, Frauke; de Bekker‐Grob, Esther
Abstract: This paper uses meta‐regression analysis to test how aspects of discrete choice experiment (DCE) study design influence survey response rates. DCEs are a survey‐based method used to elicit preferences for health and health care and are prone to survey errors of coverage, sampling, non‐response and measurement. However, research on DCE response rates is lacking. Our analysis is motivated by a social exchange theory of survey response. We find that DCE response rates are related to the survey's cognitive burden and the relevance to the surveyed population. Copyright © 2016 John Wiley & Sons, Ltd.